Do bishops matter for politics? Evidence from Italy - Gianandrea Lanzara; Sara Lazzaroni; Paolo Masella; Mara P. Squicciarini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2023)
This paper studies whether and how religious leaders affect politics. Focusing on Italian dioceses in the period from 1948 to 1992, we find that the identity of the bishop in office explains a significant amount of the variation in the vote share for the Christian Democracy party (DC). This result is robust to several exercises that use different samples and time windows. Zooming into the mechanism, we find that two characteristics of bishops matter: (i) his political culture, and (ii) his interaction with the population-the latter being measured using state-of-the-art text-analysis techniques.
Keywords: D72; Z12; D02; 330; Voting Behavior; Religion; Bishops; Leaders